KATA KERJA BANTU MODAL DALAM NOVEL â€œJUNGLE NURSEâ€ KARYA IRENE ROBERTS - Mangangantung, Nancy Dina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
Abstract In English, there are two subclasses of verbs such as lexical verb and auxiliary verb. Modals are a class of auxiliary verbs that combine with the base form to make verb phrase with a wide meaning. This study is an attempt to describe and analyze the modals in the novel ?Jungle Nurse? by Roberts. The aim of this research is to identify and classify the forms and meaning of modals and its mostly used in the novel.The method used in this research is descriptive method. The data of modals have been taken from the sentences in the novel ?Jungle Nurse? and analyzed by using Robert?s concept. The result of this study shows that modals are existed in the novel. They are pure modals, special modals, and semi modals. Pure modals used in the novel are can, could, will, would, shall, should, may, might and must. Special modals which used are be going to, have to, had better, had rather, be to, be able to, and ought to. Semi modals which used are dare and need. This study can be continually done by analyzing modals in other literary works by using the concept of Robert. ————————————————————— Keywords: Modals, English, Novel Jungle Nurse